A Causal Semantics of IS Generics. (24th February 2020) - van Rooij, Robert; Schulz, Katrin
Abstract: The felicity, or acceptability, of IS generics, i.e. generic sentences with indefinite singulars, is considerably more restricted compared to BP generics, generics with bare plurals. The goal of this paper is to account for the limited felicity of IS generics compared to BP generics, on the one hand, while preserving the close similarity between the two types of generics, on the other. We do so by proposing a causal analysis of IS generics, and show that this corresponds closely with a probabilistic analysis of BP generics.